LEGAL PROTECTION FOR CONTRACT EMPLOYMENT AT PT. SUMI RUBBER INDONESIA KARAWANG - Hidayat Hidayat (Proceedings of the 1st International Conference on Social Science (ICSS), 2022)
Legal protection is always related to government power and economic power, concerning government power, the legal protection for the people (those who are governed) against the government (those who govern). About the people, in Article 1, paragraph 3 of Law Number 13 of 2003 concerning employment, a worker or labourer is any person who works and receives wages in other forms. Workers are workers who work for employers and receive wages. The work agreement is divided into two: a specified time work agreement and an unspecified time work agreement. A contract worker works based on a work agreement for a certain time (PKWT), namely a work agreement between employers and workers to enter into a working relationship for a certain time or a certain job. Suppose in the employment agreement, the employer makes Termination of Employment (PHK), namely terminating the employment relationship because of a certain matter which results in the end of the rights and obligations of the worker. In that case, carrying out legal protection for the worker/labourer is very important. The author here will discuss issues regarding protecting the rights of contract workers who are laid off from companies and how legal remedies can be taken by contract workers who are laid off before the contract period ends. The purpose of the author, especially in the field of labour, is to prevent arbitrary termination of employment and to analyze the rights of contract workers who have been subject to Termination of Employment (PHK) before the contract period ends. The research method used is a problem approach through a statute approach and a conceptual approach. The results of the writing discussed by the author are that the party that terminates the employment relationship is required to pay compensation to the other party in the amount of the worker's salary until the expiration of the work agreement period.